Matěj Bílý, Varšavská smlouva 1985–1991. Dezintegrace a rozpad, Praha: ÚSTR, 2021 - Hryciuk, Grzegorz (Institute of National Remembrance Review, 2025)
This paper reviews Matěj Bílý’s second book on the Warsaw Pact history outlining the final years of Pact’s functioning and its demise, parallel to the demise of the Soviet Union and its domination in the Central and Eastern Europe.